The Types of Masculinity in "Me Before You" (2012) by Jojo Moyes - Rialdo Dwi Yesa; Delvy Wahyuni (English Language and Literature, 2022)
This research is an analysis of the novel by Jojo Moyes entitled Me Before You (2012). The objective of this research is to find out the forms of masculinity depicted in this novel. This study employs masculinity theory to analyzed the novel and supported by feminist theory and patriarchy theory. This a qualitave descritipve by using masculinity theory which supported by feminist literary theory and patriarchy ideologies. The results of this study shows there are several forms of masculinity depicted in this novel which are; strength, power, stoicism, action, control, independence and self-sufficiency. The result of this research shows that disability is the opposite of what is called masculine. A masculine man must have strength, power, stoicism, action, control, independence, self-sufficiency, male companionship, mateship and work.